Comparison of the performance of 3G security algorithms in the NAS layer - Yasin Ararse, Abdi-Hakim (My University, 2013)
Cryptographic functionality implementation approaches have evolved over time, first, for running security software on a general-purpose processor, second, employing a separate security co-processor ,and third, using built-in hardware acceleration for security that is a part of a multi-core CPU system. The aim of this study is to do performance tests in order to examine the boost provided by accelerating KASUMI cryptographic functions on a multi-core Cavium OCTEON processor over the same non-accelerating cryptographic algorithm implemented in software. Analysis of the results shows that the KASUMI SW implementation is much slower than the KASUMI HW-based implementation and this difference increases gradually as the packet size is doubled. In detailed comparisons between the encryption and decryption functions, the result indicates that at a lower data rate, neither of the KASUMI implementations shows much difference between encryption or decryption processing, regardless of the increase in the number of data packets that are being processed. When all the 16 cores of the OCTEAN processor are populated, as the number of core increases, the number of processing cycles decreases accordingly. Another observation was that when the number of cores in use exceeds 5 cores, it doesn’t make much difference to the number of decrease of processing cycles. This work illustrates the potential that up to sixteen cnMIPS cores integrated into a single-chip OCTEON processor provides for HW- and SW-based KASUMI implementations.
Keywords: KASUMI; 3G; UMTS security; Multi-Core; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|